2000
DOI: 10.1099/0022-1317-49-7-669
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterisation of the genes encoding glyoxalase I and II from Neisseria meningitidis

Abstract: Glyoxalase enzymes I and II are involved in a detoxi®cation process consisting of conversion of reactive dicarbonyl compounds (e.g., methylglyoxal) to less reactive hydroxy acids. The structural gene for meningococcal glyoxalase I ( gloA) was identi®ed by screening an expression library with a rabbit antiserum. The meningococcal gloA gene consisted of 138 deduced amino acids, with a calculated mol. wt of 15.7 kDa. The DNA and deduced protein sequence of gloA was compared to known sequences of glyoxalase I enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Overlapping the 3Ј end of NMA2148 is gloA (Fig. 2), a glyoxalase I gene described previously (14). One additional transposon mutant (strain 15F) displayed an identical phenotype to 276D, which was subsequently determined to have a transposon insertion in NMA2148.…”
Section: Resultsmentioning
confidence: 99%
“…Overlapping the 3Ј end of NMA2148 is gloA (Fig. 2), a glyoxalase I gene described previously (14). One additional transposon mutant (strain 15F) displayed an identical phenotype to 276D, which was subsequently determined to have a transposon insertion in NMA2148.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis of tspA (EMBL accession number AJ010113) revealed that the 2,625-bp gene encodes a protein consisting of 875 amino acids (aa) with a predicted molecular mass of 92,443 Da, a pI of 4.13, and a net charge at pH 7.0 of Ϫ85.99. In the published genome sequence of strain MC58 (serogroup B; GenBank accession number AAF40784 [39]) the gene was flanked by the lactoylglutathione lyase gene (gloA; accession number AAF40783.1 [20]) and a homolog of the intracellular septation protein gene (ispA; accession number AAF40785.1). Both flanking genes are in the opposite orientation with respect to tspA, and a promoter is predicted upstream of tspA, indicating that it is monocistronic.…”
Section: Resultsmentioning
confidence: 99%
“…Putative GlxI sequences have also been identifi ed and reported, underlining the broad occurrence of the enzyme system in Nature [57][58][59][60][61][62][63][64][65][66][67][68]. A search (as of January 2006) of the National Center for Biotechnology Information (NCBI) Protein Database reveals a diverse distribution of unique putative GlxI sequences: 70 bacterial sequences, 27 from the metazoan class, 34 fungal sequences, 8 from plant sources and 10 other eukaryotic sequences mainly from Plasmodium spp [69].…”
Section: Survey Of Glyoxalase I Enzymes From Various Sourcesmentioning
confidence: 99%
“…However it has been the detailed studies of the GlxI enzymes from human, Saccharomyces cerevisiae, rat, and Pseudomonas putida that have yielded the most detailed information at the mechanistic level [72][73][74][75][76][77]. Recently, the cloning and expression of a number of other bacterial GlxI (E. coli, Pseudomonas aeruginosa, Neisseria meningitidis and Yersinia pestis) have contributed to additional and fascinating information about the GlxI enzymes [67,78,79]. …”
Section: Survey Of Glyoxalase I Enzymes From Various Sourcesmentioning
confidence: 99%
See 1 more Smart Citation